2019
DOI: 10.1002/jcph.1412
|View full text |Cite
|
Sign up to set email alerts
|

A Phase 1, Open‐Label, Parallel‐Group, Single‐Dose Trial of the Pharmacokinetics and Safety of Cannabidiol (CBD) in Subjects With Mild to Severe Hepatic Impairment

Abstract: The pharmacokinetics and safety of a single oral dose of 200‐mg plant‐derived pharmaceutical formulation of highly purified cannabidiol (CBD) in oral solution (Epidiolex in the United States; 100 mg/mL) were assessed in subjects with mild to severe hepatic impairment (n =  8 each for mild and moderate, n = 6 for severe) relative to matched subjects with normal hepatic function (n = 8). Blood samples were collected until 48 hours after dosing and evaluated by liquid chromatography and tandem mass spectrometry. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
67
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 19 publications
5
67
0
Order By: Relevance
“…A limitation of this study is that it was performed in healthy volunteers rather than a patient cohort with the Table 5 Key pharmacokinetic parameters for the subjects Pharmacokinetic parameters were determined using Phoenix WinNonlin 8.0 AUC last area under the plasma concentration versus time curve from time zero to the last quantifiable concentration, AUC inf area under the plasma concentration versus time curve extrapolated to infinite time, C max maximum observed plasma concentration, CV coefficient of variance, GeoCV geometric mean coefficient of variance, GeoMean geometric mean, K el apparent terminal elimination rate constant, SD standard deviation, T 1/2 apparent terminal elimination half-life, T max time of maximum observed plasma concentration potential for drug-drug and drug-disease interactions. Two recent trials have documented clinically significant interactions with commonly prescribed antiepileptic drugs [15,30], while another study has reported that the metabolism of cannabidiol is significantly altered in patients with moderate or severe hepatic impairment [12]. Further limitations are that only plasma cannabidiol was measured, not its primary metabolites.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A limitation of this study is that it was performed in healthy volunteers rather than a patient cohort with the Table 5 Key pharmacokinetic parameters for the subjects Pharmacokinetic parameters were determined using Phoenix WinNonlin 8.0 AUC last area under the plasma concentration versus time curve from time zero to the last quantifiable concentration, AUC inf area under the plasma concentration versus time curve extrapolated to infinite time, C max maximum observed plasma concentration, CV coefficient of variance, GeoCV geometric mean coefficient of variance, GeoMean geometric mean, K el apparent terminal elimination rate constant, SD standard deviation, T 1/2 apparent terminal elimination half-life, T max time of maximum observed plasma concentration potential for drug-drug and drug-disease interactions. Two recent trials have documented clinically significant interactions with commonly prescribed antiepileptic drugs [15,30], while another study has reported that the metabolism of cannabidiol is significantly altered in patients with moderate or severe hepatic impairment [12]. Further limitations are that only plasma cannabidiol was measured, not its primary metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of this study is that it was performed in healthy volunteers rather than a patient cohort with the potential for drug–drug and drug–disease interactions. Two recent trials have documented clinically significant interactions with commonly prescribed antiepileptic drugs [ 15 , 30 ], while another study has reported that the metabolism of cannabidiol is significantly altered in patients with moderate or severe hepatic impairment [ 12 ]. Further limitations are that only plasma cannabidiol was measured, not its primary metabolites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cannabis has been prohibited in all sports during competition since the World Anti-Doping Agency first assumed the responsibility of establishing and maintaining the list of prohibited substances in sport 15 years ago [89]. In 2018, however, CBD was removed from the Prohibited List [199], presumably on the basis of mounting scientific evidence that the cannabinoid is safe and well-tolerated in humans [16,169], even at very high doses (e.g. 1500 mg•day −1 or as an acute dose of 6000 mg) [170].…”
Section: Introductionmentioning
confidence: 99%